Juridical Analysis Of Human Trafficking In Batam City Viewing From Human Rights - Prinelti, Maria Novianti; Wulandari, Tri Indah; Fairus, Fairus (Interdiciplinary Journal and Hummanity (INJURITY), 2022)
Violations of human rights, the cause of human trafficking must be eradicated and prevented. Due to the lack of intervention and regulation of a country, this is a very worrying condition that is very dangerous. It is difficult to bring traffickers to justice. Trafficking in persons is an act that is contrary to human rights and dignity. Trafficking in persons has become a threat to society, the nation and the state, as well as the norms of life based on respect for human rights, thanks to its spread by organized and unorganized crime networks, both within the country and between countries. This research relies on library research, also known as normative empirical research methods, and juridical research methods. The normative legal research method is a method that looks at what is already in the library. The results of the research Legislation, legal theory, and opinions of leading legal scholars are examples of secondary data sources used in juridical research methods. According to the 2010 UNAFEI report, women and children constitute one-third of all victims of human trafficking worldwide, with numbers ranging from 200,000 to 225,000 per year. To protect victims on a national and international scale, proper legal protection must be implemented. rather than the perpetrator being punished, the suffering of the victim is only used to make laws or instruments that punish the perpetrator.